2004
DOI: 10.1002/eji.200425267
|View full text |Cite
|
Sign up to set email alerts
|

Transgene‐mediated hyper‐expression of IL‐5 inhibits autoimmune disease but increases the risk of B cell chronic lymphocytic leukemia in a model of murine lupus

Abstract: IL-5 preferentially activates B1 cells to produce natural antibodies cross-reactive to self antigens. To determine the role of IL-5 in antibody-mediated autoimmune disease, we generated systemic lupus erythematosus (SLE)-prone (NZBÂNZW)F1 mice congenic for IL-5 transgene (TG-F1). The transgene unexpectedly reduced the incidence of lupus nephritis. Anti-DNA antibodies in sera and those produced by splenic B cells in vitro were markedly decreased in TG-F1 mice, while total polyclonal Ig levels were comparable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
3
21
0
Order By: Relevance
“…Supporting this latter hypothesis, it has been shown that B-1a cells do not contribute to autoantibody production in FAS-deficient mice (18). Furthermore, transgenic overexpression of IL-5 in the BWF 1 model greatly increased the number of B-1a cells, but, surprisingly, significantly reduced anti-dsDNA Ab production and incidence of nephritis (19). Finally, the NZB-derived Nba2 locus was shown to induce disease when crossed to NZW without affecting the size of the B-1 cell compartment (20), and the same observation was made for Sle1 (L. Morel, unpublished observations).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 88%
“…Supporting this latter hypothesis, it has been shown that B-1a cells do not contribute to autoantibody production in FAS-deficient mice (18). Furthermore, transgenic overexpression of IL-5 in the BWF 1 model greatly increased the number of B-1a cells, but, surprisingly, significantly reduced anti-dsDNA Ab production and incidence of nephritis (19). Finally, the NZB-derived Nba2 locus was shown to induce disease when crossed to NZW without affecting the size of the B-1 cell compartment (20), and the same observation was made for Sle1 (L. Morel, unpublished observations).…”
Section: S Ystemic Lupus Erythematosus (Sle)mentioning
confidence: 88%
“…In SLE patients with severe skin involvement, IFN-γ and IL-5 were the most commonly overexpressed cytokines in skin lesions, implying that both Th1 and Th2 subsets may be involved in the pathophysiology of SLE inflammation 92 . However, an earlier report suggests that IL-5 may play a protective role as overexpression of IL-5 in SLE-prone mice suppresses the disease 93 .…”
Section: Th2 Cellsmentioning
confidence: 97%
“…Accordingly, the removal of peritoneal B-1 cells from NZB/W F1 mice correlated with disease attenuation (Mihara et al, 1988), and osteopontin-induced B-1 cell expansion paralleled an increased anti-dsDNA Ab titers (Iizuka et al, 1998). On the other hand, B-1a cells are not responsible for autoAb production in Fas-deficient mice (Reap et al, 1993), and IL-5 induced expansion of B-1a cells in NZB/W F1 was associated with disease protection (Wen et al, 2004). …”
Section: Role Of Specific B Cell Subsets In Lupusmentioning
confidence: 99%